Desain dan Implementasi Smart Wastafel Untuk Pencegahan Penularan Covid-19: Studi Kasus di Kantor Kelurahan Sorosutan Yogyakarta - Wisudawan, Hasbi N. P.; Mubarok, Husein; Nugraha, Aditya Sandi (Proceedings Series on Physical & Formal Sciences, 2021)
Sorosutan is one of the villages in the Umbulharjo District with the largest population of 14,979 people based on statistical data in 2017. During the Covid-19 pandemic, the implementation of health protocols such as providing a handwashing area and mandatory wearing of masks is applied in all places, including public service places such as the Sorosutan Village Office. Socialization continues to be carried out by various parties so that residents can increase their self-discipline in every place and time, including when visiting these public places. The presence of officers or guards at each entrance is significant to remind residents who will enter. A large number of visitors will cause problems because it can cause long queues. In addition, the limited number of employees or personnel becomes a separate obstacle when it comes to preparing special personnel for controlling visitors. The smart sink is a solution in helping officers at the Sorosutan Village office remind residents to always wash their hands and wear masks when visiting the office. The temperature sensor installed in the sink can also help speed up temperature checking, which previously had to be done manually by officers. With the provision of this tool, it is hoped to increase public awareness so that the spread of Covid-19 can be reduced.